The levels of BMI and patterns of obesity and overweight during the COVID-19 pandemic: Experience from the Iran STEPs 2021 survey - Djalalinia, Shirin; Yoosefi, Moein; Shahin, Sarvenaz; Ghasemi, Erfan; Rezaei, Nazila; Ahmadi, Naser; Rezaei, Negar; Azmin, Mehrdad; Rezaei, Shahabeddin; Nasserinejad, Maryam; Mohammadi, Esmaeil; Haghshenas, Rosa; et al. (Frontiers in Endocrinology, 2022)
Background: Obesity and its increasing burden has become an urgent health problem all over the world. Benefiting from a national representative sample, the present study aimed to estimate the distribution of Body Mass Index (BMI) levels and its association with metabolic and lifestyle risk factors of Iranian adult population, by sex, age, and geographical distribution. Methods: It is a national survey of Non-communicable Diseases risk factor surveillance (STEPs) in Iran. Through a systematic random sampling, of the 28520 adults who gave voluntary consent and included in the study; 27874 participants completed the questionnaires (step 1), 27745 individuals were anthropometrically measured (step 2) and 18119 persons completed laboratory evaluation (step 3). Anthropometric measurements followed based on standard protocols and by using calibrated instruments. Results: In 2021, the national prevalence of normal weight, obesity, and overweight/obesity in 18≤ year-old Iranian adults was estimated at, 33.61% (95% CI: 32.99-34.23) , 24.96 % (24.39-25.53) and 63.02% (62.39-63.65), respectively. Compared to females, Iranian males had a lower mean BMI [25.54 (24.95-26.13 vs. 27.6 (27.07-28.12) kg/m2] (p < 0.001). There was also a significant difference in the national prevalence rate of overweight/obesity [F: 66% (61-71), M: 53% (46-60) (p < 0.001)]. The prevalence of obesity significantly higher in participants suffering from metabolic and lifestyle risk factors. The study of the geographical extent of obesity and overweight shows that comparing to the national the highest prevalence of being underweight was seen in the southeastern provinces. On the other hand, the highest prevalence of obesity belonged to the northeastern and central provinces. The highest provincial prevalence of obesity was almost 2.5-fold higher than the lowest provincial prevalence. Conclusion: The study reveals a significant difference between the prevalence of obesity in males and females and between different regions of country. These findings help policy makers, clinicians and researchers to more accurate estimation on obesity/overweigh problem and implementing more effective interventional programs to promote strategies of prevention and control of weight gain.